UPAYA PEMBENTUKAN KETERAMPILAN SAINS PADA ANAK USIA DINI BERBASIS SAINTIFIK - Maulina Rahayu (LPPM Universitas Bina Bangsa, 2024)
Science training in early childhood education has attracted the attention of many researchers. Although the new early childhood curriculum in Indonesia does not include specific curriculum objectives for science lessons, science is integrated into the curriculum through a “scientific approach”. There are not many articles on this topic in the media. Some articles mention the importance of this approach, while others try to find the best model to implement this approach. However, only a few articles discuss the application of this approach in depth. Therefore, this research article discusses the results of a scientific approach in three PAUD schools. This research use desciptive qualitative approach. The research results show that the use of time, the number of questions given and the teacher's questions are three important factors that influence the quality of implementing the scientific approach